2003
DOI: 10.1007/s00467-002-0986-z
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human growth hormone therapy in autosomal recessive polycystic kidney disease

Abstract: Patients with autosomal recessive polycystic kidney disease (ARPKD) may have growth retardation that is disproportionate to the degree of renal dysfunction. We treated growth-retarded ARPKD patients with recombinant growth hormone (rhGH) and document the response to therapy and effect of rhGH on the rate of progression of renal failure. The diagnosis of ARPKD and congenital hepatic fibrosis was made on the basis of clinical findings and by abdominal ultrasound examinations. Seventeen patients (6 girls/11 boys)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…These children with ARPKD who receive GH therapy for short stature, offer an interesting avenue to study the effect of GH/IGF-1 on cystic kidney disease. Interestingly, GH treatment has been shown to be effective and safe in these children as evidenced by good growth response without a detrimental effect on kidney function or kidney cyst dimensions (13).…”
Section: Discussionmentioning
confidence: 99%
“…These children with ARPKD who receive GH therapy for short stature, offer an interesting avenue to study the effect of GH/IGF-1 on cystic kidney disease. Interestingly, GH treatment has been shown to be effective and safe in these children as evidenced by good growth response without a detrimental effect on kidney function or kidney cyst dimensions (13).…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone therapy should be offered to ARPKD patients with growth failure. 55 Premature patients < 24 months with or without chronic lung disease may benefit from palivizumab administration. Inpatients with splenic dysfunction immunization against encapsulated bacteria (pneumococcus, meningococcus, and Haemophilus influenzae type B) are indicated.…”
Section: Managementmentioning
confidence: 99%
“…9 Some authors have postulated that growth retardation in ARPKD seems out of proportion to the degree of renal dysfunction, raising the question of whether there are disease-specific influences on growth. 104 However, others have reported that growth impairment is indeed correlated with decreased renal function. 105 Like children with other forms of CKD, children with ARPKD can successfully be treated with growth hormone.…”
Section: Growth Impairmentmentioning
confidence: 99%
“…105 Like children with other forms of CKD, children with ARPKD can successfully be treated with growth hormone. 104 …”
Section: Growth Impairmentmentioning
confidence: 99%